(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2019)
The aim of the present research work was to investigate the enzyme inhibitory potential of some new sulfonamides having benzodioxane and acetamide moieties. The synthesis was started by the reaction of N-2,3-dihydrobenzo[1,4]-dioxin-6-amine (1) with 4-methylbenzenesulfonyl chloride (2) in the presence of 10% aqueous Na2CO3 to yield N-(2,3-dihydrobenzo[1,4]-dioxin-6-yl)-4-methylbenzenesulfonamide (3), which was then reacted with 2-bromo-N-(un/substituted-phenyl)acetamides (6a-l) in DMF and lithium hydride as a base to afford various 2-2,3-dihydro-1,4-benzodioxin-6-yl[(4-methylphenyl)sulfonyl] amino-N-(un/substituted-phenyl)acetamides (7a-l). All the synthesized compounds were characterized by their IR and 1 H-NMR spectral data along with CHN analysis data. The enzyme inhibitory activities of these compounds were tested against -glucosidase and acetylcholinesterase (AChE). Most of the compounds exhibited substantial inhibitory activity against yeast -glucosidase and weak against AChE. The in silico molecular docking results were also consistent with in vitro enzyme inhibition data.